A Patient Who Does Not Look: A Collaborative Treatment with Video Feedback. Issue 4 (3rd July 2020) - Sandberg, Larry S.; Beebe, Beatrice
Abstract : We describe a collaborative treatment of a woman in face-to-face psychoanalytic psychotherapy (with Larry Sandberg), whose persistent gaze aversion was a symptom immune to interpretive efforts. After many years of treatment, the patient agreed to engage in video feedback sessions (with Beatrice Beebe), which have occurred for the past decade. The face of Dr. Beebe, but not the face of the patient, was videotaped during psychotherapy sessions. Dr. Beebe and the patient then reviewed segments of the videotaped session, collaboratively observing and thinking together, translating between the verbal dialogue and the therapist's implicit action dialogue. We examine the impact of this intervention on the psychotherapy process.